2018
DOI: 10.30574/gscbps.2018.2.2.0008
|View full text |Cite
|
Sign up to set email alerts
|

Community pharmacists' response to acute back pain: A simulated patient study in western region, Saudi Arabia

Abstract: Objectives: To investigate response of the community pharmacists to acute back pain consultations by the patients, using doctor of pharmacy degree (Pharm D) final year students as simulated patients. Method:The study was a cross-sectional study, conducted over a three months period from April 2016 to July 2016 in community pharmacy setting. The study was done at the western area in Saudi Arabia, at three cities: (Jeddah-Mecca-Taif). Convenient sample of 300 pharmacies were chosen. The students appeared in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(17 citation statements)
references
References 16 publications
0
17
0
Order By: Relevance
“…The target populations in all the studies were CP 28 (62.2%), 19-Boura F, Al-Tabakha M, Hassan N, Darwich M. Critical appraisal of simulated patient methodology to assess the practice of community pharmacist in the Middle East and North Africa region: A systematic review. Pharmacy Practice 2022 Jul-Sep;20(3):2701. https://doi.org/10.18549/PharmPract.2022.3.2701 3 22,24,26,29,30,[32][33][34][35]38,39,41,42,46,47,[49][50][51][52][53][54][55][58][59][60] pharmacy staff (pharmacists and non-pharmacists) 10 (22.2%), 18,23,31,36,37,43,44,48,57,60 and CP and GP 1 (2.2%). 27 Table 1 provides a summary of the descriptive characteristics of the included studies in the review.…”
Section: The Characteristics Of the Included Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…The target populations in all the studies were CP 28 (62.2%), 19-Boura F, Al-Tabakha M, Hassan N, Darwich M. Critical appraisal of simulated patient methodology to assess the practice of community pharmacist in the Middle East and North Africa region: A systematic review. Pharmacy Practice 2022 Jul-Sep;20(3):2701. https://doi.org/10.18549/PharmPract.2022.3.2701 3 22,24,26,29,30,[32][33][34][35]38,39,41,42,46,47,[49][50][51][52][53][54][55][58][59][60] pharmacy staff (pharmacists and non-pharmacists) 10 (22.2%), 18,23,31,36,37,43,44,48,57,60 and CP and GP 1 (2.2%). 27 Table 1 provides a summary of the descriptive characteristics of the included studies in the review.…”
Section: The Characteristics Of the Included Studiesmentioning
confidence: 99%
“…More than half of the studies reported the pharmacy and pharmacy staff related information 31 (68.9%). [19][20][21][22][23][24][25][26]28,29,[31][32][33]35,36,38,[41][42][43][44]46,[48][49][50][51][52]57,58,[60][61][62] Some studies got the information through direct questioning of the pharmacy representatives (manager or pharmacist in charge) 3 (6.7%), 23,25,28 or the participants whom the SP was interacting with 5(11.1%). 20,57,58,60,61 Others reported the information based on estimation 9 (20%), 19,26,31,36,38,42,49,61,61 or through surveying the participants 4 (8.9%).…”
Section: The Outcomes Measures and Major Findings Of The Included Stu...mentioning
confidence: 99%
See 2 more Smart Citations
“…The simulated patient method is a valuable research method to uncover real practice issues and is widely used in the UAE 9,10 and other countries in the region. [11][12][13][14] This method of research is often able to identify real practice challenges and lacunae in community pharmacy practice [15][16][17] and hence is employed more commonly these days.…”
Section: Introductionmentioning
confidence: 99%